Refined Use of Satellite Aerosol Optical Depth Snapshots to Constrain Biomass Burning Emissions in the GOCART Model. Issue 20 (16th October 2017) - Petrenko, Mariya; Kahn, Ralph; Chin, Mian; Limbacher, James
Abstract: Simulations of biomass burning (BB) emissions in global chemistry and aerosol transport models depend on external inventories, which provide location and strength for BB aerosol sources. Our previous work shows that to first order, satellite snapshots of aerosol optical depth (AOD) near the emitted smoke plume can be used to constrain model‐simulated AOD, and effectively, the smoke source strength. We now refine the satellite‐snapshot method and investigate where applying simple multiplicative emission adjustment factors alone to the widely used Global Fire Emission Database version 3 emission inventory can achieve regional‐scale consistency between Moderate Resolution Imaging Spectroradiometer (MODIS) AOD snapshots and the Goddard Chemistry Aerosol Radiation and Transport model. The model and satellite AOD are compared globally, over a set of BB cases observed by the MODIS instrument during the 2004, and 2006–2008 biomass burning seasons. Regional discrepancies between the model and satellite are diverse around the globe yet quite consistent within most ecosystems. We refine our approach to address physically based limitations of our earlier work (1) by expanding the number of fire cases from 124 to almost 900, (2) by using scaled reanalysis‐model simulations to fill missing AOD retrievals in the MODIS observations, (3) by distinguishing the BB components of the total aerosol load from background aerosol in the near‐source regions, and (4) by including emissions from fires too small to be identified explicitly in the satellite observations. The small‐fire emission adjustment shows the complimentary nature of correcting for source strength and adding geographically distinct missing sources. Our analysis indicates that the method works best for fire cases where the BB fraction of total AOD is high, primarily evergreen or deciduous forests. In heavily polluted or agricultural burning regions, where smoke and background AOD values tend to be comparable, this approach encounters large uncertainties, and in some regions, other model‐ or measurement‐related factors might contribute significantly to model‐satellite discrepancies. This work sets the stage for a larger study within the Aerosol Comparison between Observations and Models (AeroCOM) multimodel biomass burning experiment. By comparing multiple model results using the refined technique presented here, we aim to separate BB inventory from model‐specific contributions to the remaining discrepancies. Plain Language Summary: We compare aerosol optical depth (variable describing amount and optical characteristics of particles in the air) of open fire smoke, simulated by the Goddard Chemistry Aerosol Radiation and Transport (GOCART) global aerosol model, and the same property observed by the satellite‐borne MODIS (Moderate Resolution Imaging Spectroradiometer) instrument. We investigate if errors in the amount of biomass burning emissions (smoke) are the main reason for discrepancies between modeled and simulated aerosol optical depth. Our analysis shows that in some world regions, missing emission amount is the most important factor, whereas in other regions, small fire sources, unaccounted for in the emission inventories are more important contributors to the discrepancy. And in yet the other regions, more factors must be considered, such as model configuration or regional atmospheric dynamics or meteorological conditions to explain the difference between model and satellite. The novelty of this work includes the new method for separating background from smoke in the MODIS observations of biomass burning events. It also presents an extensive data set of almost 900 smoke cases for the use in global modeling studies. A new look at the contribution of small fires to model‐satellite comparison, and stratification of regions with different important BB‐related factors, show future directions for BB research. Key Points: Satellite snapshots of AOD provide a practical constraint for model simulations over specific biomass burning cases In different world regions the major factors affecting model‐satellite AOD discrepancy are emission amounts, missing sources, and meteorology Presented work provides the basis for multimodel analysis within AeroCom BB experiment, which will help define other BB‐relevant factors